Political Parties of Thailand – Examination for Democratic Stability - N. G. ROGOZHINA (Контуры глобальных трансформаций: политика, экономика, право, 2018)
On the threshold of elections designed to be held in February 2019,  the first after the military junta seized power in 2014, it is important  to define the role of parties in the political process of Thailand, which  as other developing countries of Asia, faces  challenges in democratic state building. The contemporary political  history of kingdom represents the confrontation of two tendencies –  authoritarianism and democracy what has a reverse impact on  political parties, their character, structure and ability to represent  interests of the society as a whole. The author analyses the process  of party evolution in the historical retrospective in the context of  transformation of political system – from bureaucratic to  semidemocratic subjected to economic modernization and changes in  socio structure of society where traditional form of organization patron-client is persisted. The author defines three  stages of evolution of party system in Thailand The first is  characterized by the full control of civil-military bureaucracy over  parties. The second stage is closely related to the formation of provincial political clientele groups. The third stage marks the  evolvement of party of “power” with the implication for  strengthening the parliamentary democracy in the beginning of XXI  century. And as the result of it – to the destabilization of political  system, based on the relative balance of power between two main  political forces – bureaucracy and army interested in reservation of authoritarian government, and bourgeoisie supporting the  liberalization of political institutes. With the emergence of party of “power” supported by the majority of population advocating  parliamentary democracy political spectrum has changed. The arising conflict of interests subjected to collision of positions  regarding the model of political governance was overcome by  military coup. Analyzing the political spectrum on the threshold of  elections the author comes to conclusion that the restoration of  compromised model of political governance sample of 80-90 years of  XX century is the most likely option of political development of  Thailand in the near future. Though it differs in one aspect – the  social structure has changed, there is the rise of that groups of population that intend to participate in the political process, what  will force the power to be more transparent and social oriented. These challenges face the political parties as well.